FORMULATION AND STABILITY OF STERILE GEL OF AGARWOOD LEAVES EXTRACT (Gyrinops Versteeg (Gilg.) Domke) FOR DIABETIC WOUNDS - Silvi Nurafni; Antonius Padua Ratu; Anisya Dwi Shakil; Siska Fitri Herdiyanti (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Agarwood leaves contain high levels of secondary metabolites due to increased metabolic processes in agarwood trees infected with fungi. Through this metabolic process, leaves contain secondary metabolites, flavonoids, and tannins. This causes agarwood leaves to have potential as an anti-inflammatory agent for treating diabetic wounds, aimed to formulate a sterile gel preparation of agarwood leaf extract and evaluate its quality, including sterility tests and stability tests (cycling tests) including organoleptic tests, homogeneity, spreadability, adhesive power, viscosity, and pH. A sterile gel formula was prepared with an extract concentration of 4% and variations of Carbopol 940 (gelling agent), namely 0.75%, 1.0%, and 1.25%. The results showed that F1, F2, and F3 were sterile and free of bacterial and fungal growth. The stability test before and after the cycling test in organoleptic tests F1, F2, and F3 were brown, had a distinctive odor of gaharu leaves, and had a soft texture. The homogeneity tests F1, F2, and F3 Homogeneous. The pH values before the cycling test were F1 5.63, F2 4.55, and F3 4.57, whereas after the cycling test, they were F1 5.05, F2 4.87, and F3 4.63. Adhesion time before cycling test F1 02.97 seconds, F2 03.15 seconds, F3 04.86 seconds while after cycling test F1 02.64 seconds, F2 03.04 seconds, F3 03.08 seconds. Spreadability test before cycling test F1 5.4 cm, F2 4.6 cm, F3 3.7 cm, while after cycling test F1 5.0 cm, F2 4.7 cm, F3 3.5 cm ...